Focusing of electron and positron bunches in plasma-dielectric wakefield accelerators - Kniaziev, R.R.; Manuilenko, O.V.; Markov, P.I.; Marshal, T.C.; Onishchenko, I.N.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2013)
The results of analytical studies and numerical simulations of wakefield excitation in a plasma-dielectric structure are presented. In the linear theory approximation (overdense plasma) it is shown that at a certain plasma density the superposition of the plasma wave and the dielectric waves allows the acceleration of the witness bunch with simultaneous focusing. Also, we carried out a PIC simulation of the underdense (“blowout”) and overdense regime of wakefield excitation in the unit.